(3MGTjI Ydi TQM QSGdI GdGSJYGQGJs - (3MSjf CafOj GdSQGFj GdEUHYjs ((3YHO Gddg Hf HTjQ GdHhSfhjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj CPGb fhY GdEfSGf MdGhI GdfWb hGdHjGfhHYO adG jNai Cf GdQSGdI GdJj YedgG CHh GdbGSe GdSeQbfOj aj JMbjb GdGSJYGQGJ HOjYI GdYHGQGJ cJH YdjgGYUGes
(3BNQgG (B:s
(3ChdG agh GdbQjfI heG ShGg JQTjM hdc Cf JLYd GdLejY bQjfI aj ebGe TOI GdGgJeGe HGdEjVGM hdPG bGd UGMH GdJdNjU GdbQjfI bO Jchf eJYOOI hGddg GdgGOjs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdHdGZIs